An edge crack with cohesive zone in the orthotropic body - Selivanov, M.F. (Reports of the National Academy of Sciences of Ukraine, 2019)
The integral equations for the problem on displacements of an edge crack in the orthotropic body and a technique of their solving are presented. The technique is exemplified by finding the stress intensity factor, which is compared with the results known from the literature. Fit rational functions are built for the obtained dependence of the stress intensity factor on the parameter of orthotropy. The problem on an edge crack in an orthotropic half-plane is also solved in the frame of a cohesive zone model with non-uniform traction—separation law.